Green Digital Education Model with AI and IoT Integration in Sustainable Goat Farming Curriculum - Arih Dwi Prihastomo; Nicholas Renaldo; Achmad Tavip Junaedi; Marice Br Hutahuruk; Muhammad Pringgo Prayetno; Umar Faruq; Jaswar Koto; Jahrizal Jahrizal; Nyoto Nyoto; Luciana Fransisca (First Ciera Publisher, 2026)
The rapid advancement of Artificial Intelligence (AI) and Internet of Things (IoT) technologies has transformed agricultural production systems; however, their integration into agricultural education remains limited. This study develops and evaluates a Green Digital Education Model that integrates AI, IoT, and Material Flow Cost Accounting (MFCA) into a Sustainable Goat Farming Curriculum. Using a Research and Development (R&D) approach, the study followed four phases: needs analysis and curriculum mapping, system development and technological integration, pilot implementation, and evaluation. IoT sensors were deployed to collect real-time environmental and livestock data, which were integrated into a cloud-based dashboard and an AI-driven Decision Support System (DSS). An MFCA module was incorporated to enable environmental cost analysis and greenhouse gas emission calculations based on standardized methodologies. Pilot implementation in selected university courses demonstrated significant improvements in students’ digital literacy, sustainability awareness, and analytical decision-making skills, as evidenced by pre-test and post-test comparisons. Qualitative findings indicated increased engagement, motivation, and interdisciplinary collaboration. The model transforms conventional livestock education into a technology-driven “living laboratory,” aligning agricultural curricula with Education 4.0 principles and sustainability reporting standards. The study contributes a scalable framework for integrating green technology and digital innovation into higher education, supporting environmentally responsible and data-driven agricultural practices.